Refining and validating change requests from a crowd to derive requirements [data] - Radeck, Leon; Paech, Barbara (Universität, 2024)
[Context/Motivation] Integrating user feedback into software development enhances system acceptance, decreases the likelihood of project failure and strengthens customer loyalty. Moreover, user feedback plays an important role in software evolution, because it can be the basis for deriving requirements. [Problems] However, to be able to derive requirements from feedback, the feedback must contain actionable change requests, that is contain detailed information regarding a change to the application. Furthermore, requirements engineers must know how many users support the change request. [Principal ideas] To address these challenges, we propose an approach that uses structured questions to transform non-actionable change requests into actionable and validate the change requests to assess their support among the users. We evaluate the approach in the large-scale research project SMART-AGE with over 200 older adults, aged 67 and older. [Contribution] We contribute a set of templates for our questions and our process, and we evaluate the approach’s feasibility, effectiveness and user satisfaction, resulting in very positive outcomes.
Gefördert durch: Carl Zeiss Foundation: P2019-01-003
Gesehen am 14.11.2024
Keywords: Forschungsdaten; Datenbank